Using Artificial Intelligence for Education in the Education 5.0 Era to Improve Reading Skills - Salam, Muhammad Yusuf; Mahayuni, Mahayuni; Taman, Mona; Mudinillah, Adam (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
This research aims to determine the use of ChatGPT for education in the Education 5.0 era in improving reading skills. ChatGPT can answer questions humanely, just like Google Nest; only Google Nest requires machines or tools like regular Google. This research uses quantitative methods, data obtained through interviews, and questionnaire distribution. Distribution of questionnaires using Google forms. The research results show that using ChatGPT for education in the Education Era 5.0 can benefit students, as evidenced by increased reading skills. From this research it can concluded that the use of ChatGPT for education has proven to be effective and efficient, the research proves this results that 80% of students have the highest scores. The limitation of this research is that the researcher only researched the use of ChatGPT for education in the Education Era 5.0 even though there are still many uses of other media that can be used as alternatives in improving students' reading skills.